The Analysis of Google Translate Translation Error From Indonesian To Arabic And Tips For Using It /Analisis Kesalahan Terjemahan Google Bahasa Indonesia-Arab Dan Tips Penggunaannya - Muhammad Nuruzzaman Syam; Rohmatun Lukluk Isnaini; Lailatu Rohmah; Sofi Naila Sa'adah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The use of Google Translate in translating Indonesian to Arabic still needs improvement. This study aims to analyze various forms of Google Translate errors in translation from Indonesian to Arabic and identify tips for using Google Translate to reduce the mistakes in translation results. This research is descriptive qualitative research using the library research method. The data analysis technique used in this research is content analysis. The discussion in this study includes a definition of translation, the urgency of translation, problematic translation and basis in translating, forms of translation errors using Google Translate, and tips for using Google Translate. The results showed that the results of the Google Translate translation from Indonesian to Arabic still cannot be said to be accurate. Several forms of errors occur, such as nakirah ma'rifat errors, mudzakkar muannats errors, errors in using meaningful harf, errors in using dhomir, mufrad errors, mutsanna jama ', errors in i'rab, errors in the use of fi'il, inaccuracies in translating the subject, predicate, conjunction, and several other positions. Several steps can be taken to minimize the mistakes in the translation results: rearranging the language structure, determining the limits of the sentences to be translated, and adjusting and editing the translation results.